Denver developmental screening test and preterm infants. Issue 1 (January 1985) - Elliman, A M; Bryan, E M; Elliman, A D; Palmer, P; Dubowitz, L
Abstract : The results of Denver developmental screening test and Griffiths mental development scales examination performed on 198 preterm children during the first three years of life and compared. Using real age the former identified children with developmental delay, but labelled up to 42% of babies as having questionable or abnormal development. Using corrected age very few children showed less than normal development, and in the first year those whose Griffiths scales results showed delay were often assessed as normal by the Denver test. In view of its less satisfactory sensitivity and selectivity it is suggested that both age lines should be drawn when using the Denver test with preterm children so that undue anxiety can be allayed while appropriate action is taken to ensure adequate follow up.